Compliance to immediate newborn care practice among midwives working in maternity wards: a best practice implementation project. Issue 3 (9th September 2020) - Kitila, Sena B.; Sudhakar, Morankar; Feyissa, Garumma T.
ABSTRACT: Background: The WHO has a series of comprehensive care instructions to improve the health of newborns from prior to conception, throughout pregnancy, soon after birth and in the postnatal period. Objective: The objective of this best practice implementation project was to promote evidence-based best practice of immediate newborn care practice among midwives working in the maternity ward. Methods: Baseline and postimplementation audits were conducted using the JBI Practical Application of Evidence System using nine audit criteria for immediate newborn care. The gaps and barriers were analyzed using Getting Research into Practice strategies based on the baseline audit result. Discussion was conducted on the identified gaps and the implementation strategies. Results: A total of 94 cases were observed for both a baseline and follow-up audit. We found that follow-up compliance rates for all criteria were improved compared with the baseline audit. For instance, criterion 5 improved from 26% during baseline to 96% during follow-up audit, and the overall average compliance at baseline was 58% and for the postimplementation audit was 96%. Conclusion: The current project revealed that training of the health professionals and presenting evidence summaries to them were strategies that resulted in improved compliance to best available evidence to immediate newborn care.